Association Between Rhode Island's Paid Family Leave Policy and Postpartum Care Use. Issue 4 (April 2021) - Steenland, Maria W.; Short, Susan E.; Galarraga, Omar
Abstract : Paid family leave was associated with an increase in attending a postpartum care visit, particularly among women from underrepresented racial groups.